Pengaruh City Branding Terhadap City Image dan Keputusan Berkunjung Wisatawan ke Kota Tebing Tinggi - Nainggolan, Anju Bherna D.; Nugraha, Riyan (STIE Bina Karya, 2025)
This study analyzes the influence of Tebing Tinggi’s city branding positioned as a stopover culinary city and the “City of Lemang” on city image and tourists’ visit decisions. The operation of the toll road has reduced the volume of stopover visits to Tebing Tinggi. Using a qualitative method through interviews, observations, and document analysis, the study finds that the city’s culinary identity remains strong, yet branding communication is not sufficiently consistent, resulting in a city image (cognitive, affective, and conative) that is less optimal in shaping tourist decisions. Brand perception, perceived value, and destination attractiveness play an important role in encouraging tourists’ stopover interest and visit decisions. These findings highlight the need for a more focused city branding strategy to strengthen city image and increase tourist visits.